Education on the Use of Black Cumin Seeds (Nigella sativa) on Metabolite Profiles, Compound Target Prediction, and Toxicity Testing in Karang Asih Village - Anwar, La Ode Muhammad; Afriyani, Annisa Esabita; Okhanza, wanda Pramudita; Nissa, Zahra Maheswari; Putri, Carina Yulia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The public still lacks understanding of black cumin seeds (Nigella sativa), especially regarding their bioactive content, benefits, and safety for consumption. To understand the proper use of herbal plants based on scientific evidence, the public needs research-based education. Therefore, this study aims to determine the education on the use of black cumin seeds in increasing public knowledge and measuring the basic health conditions of the people of Karang Asih Village. The technique used in this study was a quasi-experimental one-group pre-test-post-test design combined with a health survey. This online education was conducted through presentations, posters, and leaflets containing information on active metabolites, the mechanism of action of compounds, and scientific BSLT toxicity tests. To determine how well the participants understood, their knowledge was measured with a pre-test and post-test and analyzed with the Wilcoxon Signed Rank Test. Several parameters measured in the health survey to map the community's health conditions were blood pressure, postprandial blood sugar, total cholesterol, and body weight. Participants' knowledge increased significantly after education (p <0.001), with an average increase of 3.82 points. These results indicate that the public needs education on the safe use of herbs in accordance with clinical conditions. The results of this study can be used to support the idea that education-based research can increase public knowledge about the benefits and safety of black cumin seeds.